Penerapan integrasi pendekatan saintifik dalam Model TSTS pembelajaran matematika Siswa Kelas XI SMA Negeri 8 Makassar - Asdar Asdar; Baso Intang Sappaile; Rosidah Rosidah (Seminar Nasional LP2M UNM, 2019)
The kind of this research is pre-experiment research that aims to find out the effectiveness of Derivative learning through two stay two stray model with scientific approach of grade XI students of SMA Negeri 8 Makassar. The effectiveness of learning can be measured based on the results of students’ learning achievement, students’ activity, and students’ responses after the implementation of learning. This research was conducted in SMA Negeri 8 Makassar with an experimental unit consisting of class XI-MIPA 3 students of SMA Negeri 8 Makassar for giving treatment with the design of the research is one group pretest-posttest design. The results show that: (1) Individually, the students’ mathematics learning achievement of grade XI students of SMA Negeri 8 Makassar after implementation of Derivative learning through two stay two stray model with scientific approach is satisfied the KKM at least 75, (2) The mean scores of normalized gain after implementation of Derivative learning through two stay two stray model with scientific approach is  which is satisfied a high category, (3) the proportion of students’ mathematics learning achievement of grade XI students of SMA Negeri 8 Makassar after implementation of Derivative learning through two stay two stray model with scientific approach is not satisfied 80%. Therefore, the  implementation of Derivative learning through two stay two stray model with scientific approach is effective to be applied of grade XI students of SMA Negeri 8 Makassar based on learning achievement individually, improvement of learning achievement, students’ activity, and students’ responses. Although, inferentially for classical completeness is not satisfied with grade XI students of SMA Negeri 8 Makassar